2010
DOI: 10.1182/blood-2009-09-243139
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell function requires 12/15-lipoxygenase–dependent fatty acid metabolism

Abstract: IntroductionHematopoiesis is the process whereby the blood cell lineages are generated from a multipotent hematopoietic stem cell (HSC). HSCs possess the unique ability to self-renew but also differentiate to give rise to mature blood cells. Long-term HSCs (LT-HSCs) are the most primitive HSCs and can fully reconstitute the hematopoietic compartment of lethally irradiated animals. They reside in a hypoxic niche and are generally quiescent. 1,2 In comparison, short-term HSCs (ST-HSCs) are temporally limited in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 47 publications
3
57
1
Order By: Relevance
“…At physiological levels, low and moderate levels of ROS appear to be required for HSC activity (41)(42)(43), including early hematopoietic reconstitution after transplantation (44). However, a sustained, abnormal increase in ROS production occurs under aging (24) and genotoxic stress (45), including 5-FU chemotherapy (46), which can inhibit HSC self-renewal and induce HSC senescence and hematopoietic dysfunction (24).…”
Section: Discussionmentioning
confidence: 99%
“…At physiological levels, low and moderate levels of ROS appear to be required for HSC activity (41)(42)(43), including early hematopoietic reconstitution after transplantation (44). However, a sustained, abnormal increase in ROS production occurs under aging (24) and genotoxic stress (45), including 5-FU chemotherapy (46), which can inhibit HSC self-renewal and induce HSC senescence and hematopoietic dysfunction (24).…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyeicosatetraenoic acids (HETEs), such as 12-HETE and 15-HETE, are produced by 12/15-LOX and function as signal transducers in various situations, including inflammatory settings [38]. Loss of 12/15-LOX in HSCs induces defective hematopoiesis in a homeostatic context and repopulation deficits following transplantation, suggesting a critical role for 12/15-LOX in normal hematopoiesis and in maintaining HSC capacity [39]. In pathological settings, 12/15-LOX activity suppresses myeloproliferative disorder [40].…”
Section: Adipocytes Fatty Acid Metabolism and Hematopoiesismentioning
confidence: 99%
“…Another study shows that the level of Scd1 expression correlates with predisposition to liver carcinogenesis (6). However, the role of Scd1 in leukemogenesis and hematopoiesis remains unknown, although it has been suggested that fatty acid metabolism plays a role in leukemogenesis and hematopoiesis (14,20). In the present study, using the BCR-ABL induced CML mouse model, we found that the expression of the Scd1 gene was downregulated in LSCs and the deletion of Scd1 accelerated CML development through affecting the function of LSCs but not normal HSCs, suggesting that Scd1 plays a tumor-suppressive role in BCR-ABL leukemogenesis.…”
mentioning
confidence: 99%
“…(B-ALL) by BCR-ABL had been described previously (8,9,14,16,20,22). Briefly, in order to induce CML, donor mice were primed by intravenous injection with 5-fluorouracil (5-FU; 200 mg/kg) 4 days before collecting bone marrow cells.…”
mentioning
confidence: 99%